Kajian Potensi Dan Status Kerusakan Tanah Pada Lahan Pertanian di Kecamatan Denpasar Timur - RUKMANA, RISKA PUTRI; KUSMIYARTI, TATI BUDI; KUSMAWATI, TATIEK (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.3, Juli 2016, 2016)
The Study of Potential and of Status Soil Degradation at Agriculture Land in East of Denpasar Sub-District A study was aiming to evaluate soil degradation based on the Standard Criteria of Soil Degradation for Biomass Production under Indonesian Government Regulation No. 150 Year 2000 had done in East of Denpasar Sub-District on 2014. The study was conducted on February to July 2014, at 5 selected observation area. Selection of sampling area was done according to Stratified Purposive Sampling method. Evaluation of soil degradation was carried out as following :(1) to establish a threshold value of soil characteristics and eroded soil potential based on Standard Criteria of Soil (matching process), and (2) to determine the key factors of soil characteristics responsible for soil damage. The study results shows that: Soil condition in the entire East of Denpasar District area could be divided into two group i.e. not degraded at land unit T3 (45,35 ha) and slightly degraded at land unit T1 (248,31), land unit T2 (122,01 ha), land unit 4 (33,72 ha), and land unit 5 (19,28 ha), soil degradation caused by soil permeability.
Keywords: Potential of soil degradation; Evaluation of Soil Degradation; agriculture land